The Regional Dynamics of Integration and Citizenship Regulation: An International Comparative Perspective (IP19) - (:unkn) unknown (My University, 2025)
Regional governments compete with national and supranational actors for ownership of the regulation of immigration, asylum, and integration. Regions, Bundesländer, cantons and provinces as well as US States increasingly set their own, distinctive, policy priorities. This might lead to conflicts between governmental levels, and ultimately affects migrants’ lives. This project provides the first systematic, internationally comparative analysis of the drivers and effects of regional immigrant integration policies in multi-level systems across the world.
Keywords: regional integration policy; Europe; North America; policy analysis